Natural occurrence of a yellow mosaic disease on zucchini in India caused by a Potyvirus - R.K. SINGH, SATYA PRAKASH; R.P. PANT, S.J. SINGH, RAJ VERMA, Y.S. AHLAWAT, (Indian Phytopathology, 2003)
A potyvirus causing severe economic damage to zucchini squash was recently identified from Pune, India. The virus was isolated from leaves and fruits of zucchini (Cucurbita pepo L.) collected from commercial fields near Pune during 2001. The infected plants showed mosaic, vein banding and blotching on leaves and produced mottled, irregularly shaped blisters and filiform leaves. The virus was readily transmitted by mechanical sap inoculation. The host range of the virus was mainly confined to the members of family cucurbitaceae. The isolate incited chlorotic local lesions response on Chenopodium emerenticotor Coste and Reyn and a severe systemic mosaic on Cucurbita pepo L. The virus was transmitted by Myzus persicae and Aphis gossypii in a non-persistent manner. Electron microscopic observations of the leaf dip and purified preparations revealed the presence of long, filamentous, not enveloped usually flexuous virus particles measuring between 700-750 nm. In serological tests through ELISA, the virus reacted strongly with the antiserum of Zucchini yellow mosaic virus (ZYMV). On the basis of symptomatology, host range, aphid transmissibility, serology and particle morphology the virus isolate was found closely related to ZYMV.